2019
DOI: 10.1111/tran.12353
|View full text |Cite
|
Sign up to set email alerts
|

Relations of sovereignty: The uneven production of transnational plantation territories in Laos

Abstract: The contemporary emergence of land grabbing across the Global South has been framed by critics as a threat to the national territorial sovereignty of postcolonial societies. Such concerns hinge on conventional notions of sovereignty as an abstract form of power possessed by the state and lost to global forces. However, the transfer of domestic lands into the hands of foreign investors is complicated by the contested and relational nature of authority in resource frontier spaces. Critical scholarship has shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This research has for example argued that sovereignty is socially constructed (i.e. Kenney-Lazar, 2020;Sidaway, 2003;Richardson, 2019), performed across a multitude of registers and norms (i.e Perazzone, 2019;Mountz, 2010) and continually formed (i.e Hagmann & Péclard, 2010;Dittmer, 2020). Herein I focus specifically on two sets of conversations in the literature that explore the ways that the state is produced in the everyday-namely the research on 'New Statecraft' stemming from Political Geography (drawing primarily on empirical data from the Global North) (see for example Dittmer, 2020;Painter, 2011Painter, , 2006Colona, 2020) and research on the 'Everyday state/Everyday Governance' emerging from Southern Urban Studies and the anthropological study of the State in the Global South (see for example the edited volume of Fuller & Benei, 2000;Le Meur & Lund, 2001;Oliver de Sardan, 2014;Perazzone, 2019).…”
Section: Understanding the State-disciplinary Overlap Without Convers...mentioning
confidence: 99%
“…This research has for example argued that sovereignty is socially constructed (i.e. Kenney-Lazar, 2020;Sidaway, 2003;Richardson, 2019), performed across a multitude of registers and norms (i.e Perazzone, 2019;Mountz, 2010) and continually formed (i.e Hagmann & Péclard, 2010;Dittmer, 2020). Herein I focus specifically on two sets of conversations in the literature that explore the ways that the state is produced in the everyday-namely the research on 'New Statecraft' stemming from Political Geography (drawing primarily on empirical data from the Global North) (see for example Dittmer, 2020;Painter, 2011Painter, , 2006Colona, 2020) and research on the 'Everyday state/Everyday Governance' emerging from Southern Urban Studies and the anthropological study of the State in the Global South (see for example the edited volume of Fuller & Benei, 2000;Le Meur & Lund, 2001;Oliver de Sardan, 2014;Perazzone, 2019).…”
Section: Understanding the State-disciplinary Overlap Without Convers...mentioning
confidence: 99%
“…In her assessment of this project, Wanjing Chen (2020: 10) concluded that the Chinese central state ‘tends to set up high‐profile developmental schemes without resolving the quotidian processes needed to bring these visions into reality from the onset.’ Moreover, agreements that are signed between national authorities and Chinese state or private actors may not be feasible on the ground. In his study of Chinese rubber plantations in Laos, Miles Kenney‐Lazar (2020) found that the private Chinese company Sun Paper struggled to gain access to the full spatial extent of its land concession agreement because sub‐national Lao authorities supported local villagers who contested their dispossession. In this case, the strong connection between sub‐national state authorities and villagers, informed by their shared political histories, was more influential in determining the outcome of Chinese investment than an agreement from national levels of government.…”
Section: Chinese Infrastructure As Spatial Fix?mentioning
confidence: 99%
“…The nation‐state is often perceived as an extractive entity, rather than protective force (Hagmann & Korf, 2012; Rodgers, 2006; Tilly, 1985). Sovereign anxiety in Myanmar is shaped by these trends and other local power relations that we examine in subsequent sections – just as in practice, there is no ‘pure’ de facto sovereignty, but rather evolving power dynamics that produce sovereignty as an effect (Kenney‐Lazar, 2020).…”
Section: Towards An Emotional Geopolitics Of Infrastructurementioning
confidence: 99%
“…Recent literature emphasises that spaces of sovereignty are ‘produced and transformed by a range of contested and consensual relations among heterogeneous actors and entities’ (Kenney‐Lazar, 2020, p. 333). In Myanmar, CMEC projects are spaces of sovereignty constituted not only by consensual relations between the Chinese and Myanmar leaders, but also by the contestations of local inhabitants, civil society actors, and government officials themselves.…”
Section: Relations: Secrecy Fatalism and Insecure Attachmentsmentioning
confidence: 99%